(untitled) (Ius Novum, 2026)
The legislator, under the Act on Access to Public Information, introduced a distinction between simple and processed information. Processed information is understood as information that, as at the date of submitting the request, does not exist in a form expected by the requester and, therefore, has to be specially generated for the requester’s needs. Provision of processed information is conditional upon the requirement of particular importance for the public interest. A special category of public information, access to which is governed by a separate legislative act, is environmental information. Under the Act on the Provision of Information on the Environment and its Protection, Public Participation in Environmental Protection and Environmental Impact Assessments, however, the legislator has not introduced any provisions on access to processed information. This gives rise to a practical problem as to how an entity obliged to provide information should react if it receives a request for environmental information whose nature indicates that, in fact, processed information has been requested. The purpose of this article is to resolve this practical issue through a dogmatic analysis of the provisions of both aforementioned Acts in the light of relevant axiological considerations. This is the case as the opinions presented in the literature so far seem to conflict with fundamental constitutional values.